Investigation of Uterine Contractility and Myometrial Stiffness in Pelvic Organ Prolapse - Aslan, Melike Baspinar; Kacar, Emine; Artas, Hakan; Onat, Miray; Eryesil, Hasan; Narcicegi, Veziha Kaya; Atilgan, Remzi (Dove Medical Press Ltd, 2026)
Purpose: Pelvic organ prolapse (POP) is a common condition affecting women's quality of life. The pathophysiology of POP is complex and not yet fully understood. This study aimed to investigate uterine contractility and myometrial stiffness in patients with POP. Patient Methods: The study included 27 POP patients and 27 non-POP patients scheduled for hysterectomy. Preoperatively, transabdominal shear wave elastography (SWE) examinations were performed. During hysterectomy, myometrial tissues were collected and suspended in isolated organ baths. Peak-to-peak (p-p) contractions, the area under the curve (AUC), and frequency changes before and after oxytocin application were normalized as percentage changes between the two groups. Results: No significant differences were observed in SWE measurements between the groups. When uterine contraction measurements were compared after oxytocin administration, frequency, p-p, and AUC values were statistically significantly reduced in the POP group compared to the non-POP group (p < 0.05). Conclusion: An association was observed between decreased uterine contractility and POP. The results obtained in the present study suggest that decreased uterine contractility may be a risk factor for the development of POP.
Keywords: pelvic organ prolapse; isolated organ bath; shear wave elastography; uterine contractility